2017
DOI: 10.4067/s0718-50062017000100007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del Aprendizaje Basado en Problemas en Estudiantes Universitarios de Construcciones Agrarias

Abstract: ResumenEn este trabajo se exponen los resultados de una aplicación y evaluación de la Metodología didáctica específica denominada Aprendizaje Basado en Problemas (ABP) en estudiantes de Construcciones Agrarias. El trabajo se ha efectuado durante el curso 2015-16 en dos grupos de alumnos del Grado de Ingeniería Agrícola de la Escuela Técnica Superior de Ingeniería de la Universidad de Huelva (España). El estudio incluyó la aplicación de la metodología didáctica específica y su evaluación. La evaluación se ha ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
0
5
0
5
Order By: Relevance
“…In engineering, the majority of research related with the use of this method has sought to analyse its influence on the development of student's critical thinking, training and development of professional skills, conceptual understanding of learning content and the obtainment of meaningful gains in the learning of content. All of this is manifested as improved academic performance (Fernández & Duarte, 2013;Yadav, Sumedi, Lundeberg & Bunting, 2011;Rodríguez & Fernández-Batanero, 2017;amongst others).…”
Section: Introductionmentioning
confidence: 99%
“…In engineering, the majority of research related with the use of this method has sought to analyse its influence on the development of student's critical thinking, training and development of professional skills, conceptual understanding of learning content and the obtainment of meaningful gains in the learning of content. All of this is manifested as improved academic performance (Fernández & Duarte, 2013;Yadav, Sumedi, Lundeberg & Bunting, 2011;Rodríguez & Fernández-Batanero, 2017;amongst others).…”
Section: Introductionmentioning
confidence: 99%
“…A la vez, aspectos evaluativos y su puesta en práctica son reconocidos como elementos de calidad y de una correcta gestión en procesos de formación bajo la modalidad del e-learning, como lo respaldan Carmona, Arrieta, y Rodríguez (2015), Castillo, García, Corredor, y Malaver (2017), REVISTA ELECTRÓNICA CALIDAD EN LA EDUCACIÓN SUPERIOR ISSN: 1659-4703, VOL. 10(1) ENERO -JUNIO, 2019: 58 -95 http://investiga.uned.ac.cr/revistas/index.php/revistacalidad Correo electrónico: revistacalidad@uned.ac.cr __________________________________________________________________________________________________________________________________________ _____________________________________________________________________________________________________________ Estado del arte de la evaluación de los aprendizajes en la modalidad del e-learning desde la perspectiva de evaluar para aprender, algunas precisiones conceptuales Francisco Mora-Vicarioli DOI: http://dx.doi.org/10.22458/caes.v10i1.2453 Artículo protegido por licencia Creative Commons 81 García (2014), Huber (2017), Marciniak, y Sallán (2017), Martínez (2017), Morales (2016), Noche, Serra, Ruiz e Ibáñez (2017), Rincon y Bedoya (2017), Rodríguez y Fernández (2017), Romero, Castejón, López y Fraile (2017), Calvo y Galaup (2017), Chávez (2017), Ryan (2015), Terry, Heitner, Miller, y Hollis (2017) y Zúñiga, Solar, Lagos, Báez, y Herrera (2014.…”
Section: Evaluar Para Aprenderunclassified
“…The results suggested that learning with various representations could stimulate the students to be actively engaged to solve chemical problems especially to interpret and transform macro, sub-micron, and symbolic phenomena. Through the exercises of various learning models, the students acquired easier ways to under-stand the chemistry concepts deeply (Rodríguez & Fernández-Batanero, 2017) and stronger ability to perform meaningful reasoning of chemical phenomena (Coll, 2008;Sunyono & Sudjarwo, 2018).…”
Section: Based Onmentioning
confidence: 99%
“…Previous studies showed that learning using PBL can improve students' conceptual understanding. Rodríguez & Fernández-Batanero (2017) stated that PBL is one of the learning models that can motivate students to learn chemistry. The research of Kelly & Finlayson (2007) concluded that chemistry learning using PBL model could provide an excellent scope of learning for the development of skills, understanding of chemistry concepts, and laboratory experiment processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation